Blunted furosemide action on cerebellar GABA-A receptors in ANT rats selectively bred for high alcohol sensitivity - Makela,R; Lehtonen,M; Wisden,W; Luddens,H; Korpi,ER (Neuropharmacology, 1996)
Furosemide specifically reverses the inhibition by gamma-aminobutyric acid (GABA) of t-[35S]-butylbicyclophosphorothionate ([35S]TBPS) binding and increases the basal [35S]TBPS binding to the cerebellar granule cell layer GABAA receptors. For the selectivity of furosemide, an interplay between GABAA receptor alpha 6 and beta 2 or beta 3 subunits is needed. We have now investigated the furosemide sensitivity of cerebellar [35S]TBPS binding in the alcohol-sensitive (ANT) rat line that harbors a pharmacologically critical point mutation in the alpha 6 subunit [alpha 6 (Q1000)], increasing benzodiazepine affinity of the normally insensitive alpha 6-containing receptors. ANT receptors were less efficiently affected by furosemide, while a normal GABAA receptor antagonism was observed with a specific GABAA receptor antagonist SR 95531. Reduced [3H]muscimol binding in ANT samples and small alterations in situ hybridization signals for alpha 1, alpha 6, beta 2, beta 3, gamma 2 and delta subunit mRNAs failed to correlate with impaired cerebellar furosemide efficacy in individual animals. The alpha 6 (q100) ANT mutation was not responsible for the reduced efficacy of furosemide in the ANT rat line, as judged from the potent furosemide antagonism in recombinant ANT-type alpha 6 (Q100)beta 3 gamma 2 receptors. This data suggest that presence of a novel abnormality in the structure and/or expression of alpha 6 subunit-containing GABAA receptors in the ANT rat line.